Reducing intravenous thrombolysis delay in acute ischemic stroke through a quality improvement program in the emergency department - Yuan, Guangxiong; Xia, Hong; Xu, Jun; Long, Chen; Liu, Lei; Huang, Feng; Zeng, Jianping; Yuan, Lingqing (Frontiers in Neurology, 2022)
Objective This study aims to investigate the effectiveness of a quality improvement program for reducing intravenous thrombolysis (IVT) delay in acute ischemic stroke (AIS). Materials and methods We implement a quality improvement program consisting of 10 interventions for reducing IVT delay, including the establishment of an acute stroke team, standardized management of stroke teams, popularization of stroke and its treatment, emergency bypass route (BER), the achievement of computed tomography (CT) priority, no-delay CT interpretation, intravenous thrombolysis on the CT table, payment after treatment, whole recording, and incentive policy. We retrospectively analyzed the clinical time and outcome data of AIS patients treated with IVT in pre-intervention (108 patients) and post-intervention groups (598 patients), and further compared the differences between the non-emergency bypass route (NBER) and BER in the post-intervention group. Results The thrombolysis rate increased from 29% in the pre-intervention group to 48% in the post-intervention group. Compared with the pre-intervention group, the median of door-to-needle time (DNT) was greatly shortened from 95 to 26 min (P < 0.001), door-to-CT time (DCT) was noticeably decreased from 20 to 18 min (P < 0.001), and onset-to-needle time (OTT) significantly declined from 206 to 133 min (P = 0.001). Under the new mode after the intervention, we further analyzed the IVT delay difference between the NBER (518 patients) and BER groups (80 patients) from the post-intervention group. The median values of DNT (18 vs. 27 min, P < 0.001), DCT (10 vs. 19 min, P < 0.001), and OTT (99 vs. 143 min, P < 0.001) showed significant reductions in the BER group. The quality improvement program under the emergency platform successfully controlled the median of DNT to within 26 min. Conclusions Collectively, the BER mode is a feasible scheme that greatly decreased DNT in AIS patients, and the secret to success was to accomplish as much as possible before the patient arrives at the emergency room.